SELEKSI JAMUR PELAPUK PUTIH HUTAN TROPIS INDONESIA SEBAGAI PENGHASIL ENZIM LAKASE (Lac) DAN MANGAN PEROKSIDASE (MnP) - Lisna Efiyanti; Asep Hidayat (BRIN Publishing, 2017)
White-rot fungus, Basidiomycetes is an unique group of microbes among the major decomposers of plant polymers or biomass. Their existences are under pressure due to Indonesian tropical forests degradation caused by forest fires, excessive exploitation, land conversion and biopiracy. Based on natural process of white rot fungi, it could be utilized for bioresources, i.e improvement of food quality and leading of new functionality (the food industry), delignification (pulp & paper), production of ethanol (biofuel), biosensors and bioremediation. This paper studies isolate, selection and evaluation of the potential extracellular enzymes laccase (Lac) and manganese peroxidase (MnP) from fungi grown in Indonesian tropical forest. A total of 178 samples of fungi fruit were collected from Indonesian tropical forest, including West Java, East Java and East Kalimantan Provinces, then they were isolated and selected on RBBR agar media for futher analysis. The results showed that there were significant differences of 26 pure isolates, in term of its capacity to decolorize RBBR, and only six pure isolates (JB-7.1.1, BST-F16, Gr-W3.2A-C, TRK-1, TRK-2, and TRK-3) were able to oxidize RBBR more than 1 cm per day. Futhermore, two isolates were selected as their enzymes production was higher than another, those were -1-1 JB-7.1.1 (Lac = 526 ± 142 UL and MnP = 114 ± 13 UL ), and TRK-2 (Lac = 463 ± 95 UL and MnP = 98 -1-1 ± 8 UL ). Statistically, the activity of Lac produced by JB-7.1.1 was higher and not significantly different with the positive control, Cerrena sp. F0607. JB-7.1.1 and TRK-2 isolates were the potential fungi for producing Lac, which they could be applied easily for textile dyes decolorization as bioremediation.